Sistem Keamanan Kendaraan Bermotor Berbasis IoT dan Web dengan Fitur Pelacakan GPS dan Pemutusan Aliran Listrik Secara Otomatis - Tofiq Nur Hidayat; Farida Ardiani (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
In general, motorcycle vehicles only have security such as conventional safety locks or only an alarm system. Unlike vehicles such as modern cars that already have GPS (Global Positioning System) devices. There are many ways to improve motorized security systems, one of which is embedding GPS devices in vehicles that do not yet have similar security. So Internet of Things (IoT) technology and GPS devices such as Ublox Neo are used to help monitor the whereabouts of vehicles in real time. IoT technology allows smart sensors to be connected to the internet network. Tracking systems that use IoT can utilize data from sensors to provide information to users about the whereabouts of their vehicles. the use of this technology aims to increase efficiency and security on vehicles so that cases of vehicle theft rates can be suppressed. The results of the test there are several conditions when the device cannot work properly. However, 80% of the test results show the success of the device in tracking vehicles. The average response time in receiving satellite data is about 1-5 seconds. The user can also turn off the vehicle so that the user can more easily chase the perpetrator so as to minimize the occurrence of vehicle theft. the response time of the device in turning off the vehicle is about 5-10 seconds due to alternating in sending and receiving data with the GPS module. It is hoped that criminals who steal vehicles will find it more difficult to steal motorcycles equipped with IoT-based security systems.